Francisco antonio cano: escultor y maestro de la escuela nacional de bellas artes - Fajardo, Marta (CALLE14: revista de investigación en el campo del arte, 2011)
The teacher Francisco Antonio Caro (Yarumal, 1865 – Bogotá, 1935) was the first Colombian artist to exercise sculpture in a professional way. From his professorship, he taught the foundations of his work and responded with efficiency to public and private responsibilities. Although he is recognized as one of Colombian’s more outstanding painters of his generation, his work as sculptor has not been equally valued. Our purpose is to point out Cano’s most significant contributions to commemorative and ornamental sculpture which, besides enriching spaces and places of Bogotá and other cities, exercised a remarkable educational work directed as much toward the people of the city as to his students in the National School of Fine Arts.